A case study of rapid growth in the Mopani district of the Seventh-day Adventist Church - Tumelo Silas Motsie (Institut Agama Kristen Negeri Toraja, 2025)
The Seventh-day Adventist Church in South Africa has experienced significant growth in the Trans-Orange Conference Districts between August 2023 and December 2024. This article examines the contributions of the districts and that of Pastor Mavuso to this expansion, highlighting his methodologies and the resultant numerical and qualitative growth of the church in these regions. The study has deduced that, although the church is growing numerically (Mopani district, which is a case study, has surpassed its target and is thus assisting in the overall conference target being achieved), it may not necessarily be growing qualitatively in terms of the quality of believers produced. The accountability of most of the baptised individuals is problematic, as several factors contributing to this issue may not be known to the church. The study has concluded that the strategies used in the Mopani district were designed primarily to convert people from their denominations to Adventism, instead of making them disciples of God. Therefore, numerical growth is not a sign of spiritual growth.